2006
DOI: 10.2134/agronj2005.0210
|View full text |Cite
|
Sign up to set email alerts
|

A Library to Generate Synthetic Precipitation Data

Abstract: A critical issue in biophysical modeling projects is to develop a set of reusable libraries to support the development of future applications. This is true for weather modeling as well. Rain is a software component providing a collection of stochastic approaches to generate precipitation data on daily and subdaily time steps. Synthetic data generated on a daily time step consists of precipitation occurrence and amount. Subdaily generation includes time of peak, peak intensity, storm arrival, and duration. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Garbrecht and Zhang (2003) showed that because of inherent characteristics of random number generators, screening the generated precipitation to ensure representation of the climate of interest allows for shorter simulation duration and greater ability to simulate subtle changes in precipitation such as those associated with seasonal forecasts. Carlini et al (2006) developed a library to generate synthetic precipitation data for future crop modeling applications.…”
Section: Historical Overview and Discussionmentioning
confidence: 99%
“…Garbrecht and Zhang (2003) showed that because of inherent characteristics of random number generators, screening the generated precipitation to ensure representation of the climate of interest allows for shorter simulation duration and greater ability to simulate subtle changes in precipitation such as those associated with seasonal forecasts. Carlini et al (2006) developed a library to generate synthetic precipitation data for future crop modeling applications.…”
Section: Historical Overview and Discussionmentioning
confidence: 99%
“…In order to possibly include legacy data sources into newly developed systems, object-oriented development has emerged steadily as a paradigm that focuses on granularity, productivity, and low maintenance [3]. Several papers have been recently published in agroecological journals [4][5][6][7][8][9][10] targeting at reusable dynamic link libraries either within the Microsoft.NET framework (http://www.microsoft.com/NET/) or using the SUN Java platform (http://java.sun.com/). Such solutions reflect a style of programming referred to as component-oriented programming that has become the leading methodology in developing systems in a variety of domains, including agroecological modeling [2].…”
Section: Introductionmentioning
confidence: 99%
“…This is the reason why component-oriented tools have been recently developed to fit this need, that is, ET for calculating evapotranspiration and related variables [5], GSRad for estimating synthetic values of solar radiation [6], Rain [4] for generating precipitation data, and Wind [9] for generating wind speed data. The components mentioned provide a set of alternate models to estimate variables specific for the domain targeted and are implemented using a software architecture which promotes reusability [21].…”
Section: Introductionmentioning
confidence: 99%